Pembuatan Media Pembelajaran Berbasis Crossword Puzzle Pada Pembelajaran Tematik Terpadu Di Kelas V Sekolah Dasar - Vivi Puspita; Shella Marcelina (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This research is motivated by the lack of use of learning media when giving assignments to students at home. So that it makes students less enthusiastic about studying at home. For this reason, the researcher wants to develop crossword puzzle based learning media on theme 3, sub-themes 1, learning 1 and 2 class V SD. This crossword puzzle media is in the form of a game that is done by filling in the empty spaces in the form of empty boxes with letters to form a word that matches the instructions for the question. The purpose of this development is to develop crossword puzzle media and to find out the validity and practicality of the crossword puzzle media to be used. This research is an R&D research using the 4D model, namely define, design, developement, and desseminate. However, due to the covid-19 condition, researchers only conducted limited research. The results showed that the average value of validity was 3.63 (very valid). this shows that the crossword puzzle media is very feasible to use. While the practicality of the crossword puzzle media, the average value of the 3 questionnaire responses of students was 3.71 (practical). In conclusion, crossword puzzle based learning media on theme 3, sub-themes 1, learning 1 and 2 are valid and practical so that they can be used as learning media in grade V SD